Apathetic symptom presentations in patients with severe traumatic brain injury: Assessment, heterogeneity and relationships with psychosocial functioning and caregivers' burden. (6th December 2015) - Arnould, Annabelle; Rochat, Lucien; Azouvi, Philippe; Van der Linden, Martial
Abstract: Objectives : Apathy is frequently described following traumatic brain injury (TBI) and defined on the basis of three dimensions (emotional blunting, lack of initiative, lack of interest), which are commonly assessed by the Apathy Inventory (AI). The aims were (1) to explore the psychometric properties of this scale in the TBI population and the relationships between the dimensions; and (2) to determine whether sub-groups of patients differing with respect to the three AI dimensions could be identified and to examine their differences on psychosocial functioning and caregivers' burden. Participants and measures : Close relatives of 68 patients with severe TBI were given the AI and two questionnaires to assess their subjective burden and patients' changes in psychosocial functioning. Results : The scores distribution and the sensitivity of each sub-scale showed that the AI can be used as a screening tool in the TBI population. Four clusters were identified: one group with high scores on each dimension, one group with low scores on each dimension, one group with high emotional blunting alone and another with elevated lack of initiative/interest. The high apathetic group and the lack of initiative/interest group were associated with poorer psychosocial functioning and the high apathetic group was related to subjective burden. Conclusions : These results shed new light on the concept of apathy in patients with TBI and underline the necessity to take into account the various profiles of symptoms of apathy.